2013
DOI: 10.1590/s0034-737x2013000100016
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibilidade de espécies de plantas com potencial de fitorremediação do herbicida sulfentrazone

Abstract: Selection of plants tolerant to sulfentrazone and potential for phytoremediationAmong the new technologies, phytoremediation is considered as an option for the decontamination of areas that thave undergone intense herbicide applications. This work aimed to select species with potential to the phytoremediation of soils contaminated with the herbicide sulfentrazone. The tested species were Calopogonium mucunoides, hybrid Sorghum (Sorghum bicolor x Sorghum sudanense), Crotalaria breviflora, Crotalaria juncea, Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 20 publications
4
15
0
6
Order By: Relevance
“…The potential of C. juncea and C. ensiformis to phytoremediate soils contaminated with up to 400 g ha -1 sulfentrazone has already been confirmed (MADALÃO et al, 2013), and the results of the present study underline the capacity that these plant species have to decontaminate soil contaminated with this herbicide up to a dose of 800 g ha -1 a.i. The results further show the contribution of the phytoremediation technique to increase the production of P. glaucum grains.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The potential of C. juncea and C. ensiformis to phytoremediate soils contaminated with up to 400 g ha -1 sulfentrazone has already been confirmed (MADALÃO et al, 2013), and the results of the present study underline the capacity that these plant species have to decontaminate soil contaminated with this herbicide up to a dose of 800 g ha -1 a.i. The results further show the contribution of the phytoremediation technique to increase the production of P. glaucum grains.…”
Section: Resultssupporting
confidence: 76%
“…In a bioassay conducted by Belo et al (2011) using sorghum as an indicator plant, Helianthus annuus was the highest performer in reducing carryover effects. In turn, Madalão et al (2013) selected the green manure Canavalia ensiformis, Crotalaria juncea and Dolichos lablab as having potential for phytoremediation. Such results show the environmental viability of applying phytoremediation to sulfentrazone-contaminated soils.…”
Section: Introductionmentioning
confidence: 99%
“…This demonstrates a better performance of the parameter "root" than the others. The root size is an important feature in order to phyto-stabilize the areas contaminated by heavy metals, for it protects the soil from erosion, reduces lixiviation, favors aggregation and microbiological activity in the soil (MADALÃO et al, 2013). PINTO et al (2011) analyzed the nutritional efficiency of Eucalyptus clones.…”
Section: Rootmentioning
confidence: 99%
“…Research has identified the jack bean (Canavalia ensiformis) as an efficient species for the remediation of sulfentrazone, under controlled conditions (Madalão et al 2012;Madalão et al 2013).…”
Section: Introductionmentioning
confidence: 99%